Characteristics of the Physicochemical Properties of Sago and Banana-Based Snack Bars as Functional Foods - Koja, Reni; Wellyalina; Abdi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Snack bar is one of the most suitable products for ready-to-eat food. This research aims to develop a snack bar made from sago flour and banana with the substitution of tempeh flour as the protein source. This research used an exploratory method consisting of 4 treatments and 3 replications. The treatment used is the difference in the ratio of using sago flour and tempeh flour in 1:1, 2:1, 1:2, and control treatment (wheat flour), making snack bars. The result show that for water content (16-17%), ash (0.52 - 0.78%), fat (13.78-17.89%), protein (2.45-8.68%.) carbohydrate (56.62-65.73%), fiber (0.24-0.78%), total energy (396.71-422.22 kcal), hardness (152.02-215.06 N/cm2), color (L value 26.51-44.33), and organoleptic test with parameters tested were the color, taste, aroma and texture of the snack bar. The formulation using sago, tempeh, and banana flour can be used as a reference for making snack bar formulas as functional foods that contain complex nutrients and are useful as a source of energy for the body. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-beingSDG 12: Responsible Consumption and Production